Extracción de pectina líquida a partir de cáscaras de maracuyá (passiflora edulis) y su aplicación en el desarrollo de un producto de humedad intermedia - Rivadeneira, M. (2010)
This work aims to benefit from the availability of waste from processing plants passion fruit concentrate, focus on obtaining liquid pectin extract under optimal conditions. Pectin is a technologically functional of interest to the food industry in product development for its rheological properties that are favorable for the development of different products providing texture and consistency. For the extraction of pectin liquid treatment studies and analysis of passion fruit peel as raw material, using a variety flavicarpa Passiflora edulis, in addition to the process of gelling material obtained through laboratory experimentation method patents based on acid hydrolysis, determining appropriate parameters such as temperature, pH and time affect the quality evident in galacturonic acid content and degree of esterification, resulting in their ability to gel. This research also includes the application in the development of an intermediate moisture food such as pineapple jam, building design formula combinations thrown by the factors corresponding to percentage of fruit and extract at different levels providing three treatments were analyzed sensory.